1991
DOI: 10.1039/p19910002054
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic synthesis of some macrocyclic C13-lactones

Abstract: Oxidation of linoleic acid using immobilised soybean lipoxygenase-I gave (1 3s) -1 3-hydroxyoctadeca-9,11 -dienoic acid 1 : lactonisation and Diels-Alder reactions involving this hydroxy acid have been explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Methyl (11S,12S)-epoxy-13S-hydroxy-9Z-octadecenoate 2 {[α] D 25 +4.5°(c 1.0, CHCl 3 ), the erythro isomer, 84% de} was the major product. The erythro assignment of compound 2 was supported by the 1 H NMR shift of the hydroxyl proton of C13 at δ H 4.01 ppm [12], and the coupling constant J = 3.21 Hz confirmed that the adjacent proton of alcohol (C13) and epoxy proton at C12 were in the erythro configuration [14]. On the other hand, the titaniumcatalysed epoxidation of methyl 13S-HODE with TBHP in the presence of D-DIPT afforded methyl (11R,12R)-epoxy-13S-octadecenoate 3 {[α] D 25 +2.1°(c 1.0, CHCl 3 ), the threo isomer, 76% de} as a predominant product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl (11S,12S)-epoxy-13S-hydroxy-9Z-octadecenoate 2 {[α] D 25 +4.5°(c 1.0, CHCl 3 ), the erythro isomer, 84% de} was the major product. The erythro assignment of compound 2 was supported by the 1 H NMR shift of the hydroxyl proton of C13 at δ H 4.01 ppm [12], and the coupling constant J = 3.21 Hz confirmed that the adjacent proton of alcohol (C13) and epoxy proton at C12 were in the erythro configuration [14]. On the other hand, the titaniumcatalysed epoxidation of methyl 13S-HODE with TBHP in the presence of D-DIPT afforded methyl (11R,12R)-epoxy-13S-octadecenoate 3 {[α] D 25 +2.1°(c 1.0, CHCl 3 ), the threo isomer, 76% de} as a predominant product.…”
Section: Resultsmentioning
confidence: 99%
“…13S-HODE (1) was prepared from linoleic acid (Sigma, Dorset, UK) through a chemoenzymatic procedure [12] followed by methylation with diazomethane. 13S-HODE 1 (100 mg, 0.32 mmol) was transferred into a pear-shaped flask containing freshly distilled dichloromethane (10 ml) and molecular sieves (4 Å, 10 mg, Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…In the field of lactones, Maguire et al ( 1991 ) achieved the reaction of lactonization of the linoleic acid employing an immobilized soybean lipoxygenäse leading to a C13 macrocyclic lactone as a product. Willets e/ai.…”
Section: Other Oxidoreductasesmentioning
confidence: 99%
“…Many studies have already reported on immobilization of enzymes related to the oxylipin pathway, such as the immobilization of LOX, using the adsorption method, on glutenin and gliadin as well as on glass and glass wool [6,7]. Several methods were developed to covalently immobilize LOX with cyanogen bromide (CNBr), glutardialdehyde (GDA) and oxirane acrylic beads; however, these methods failed to stabilize the enzymes [8,9]. Rice husk silica is known to be an efficient matrix for protein immobilization, owing to its nanoporous structure (pore size approximately 4-5 nm) and the availability of functional groups on the silica surface [10][11][12].…”
Section: Introductionmentioning
confidence: 99%